2015
DOI: 10.1111/lam.12493
|View full text |Cite
|
Sign up to set email alerts
|

Detection of β-exotoxin synthesis in Bacillus thuringiensis using an easy bioassay with the nematode Caenorhabditis elegans

Abstract: In this work, we implemented a qualitative and fast bioassay using the nematode Caenorhabditis elegans to detect the production of β-exotoxin in different strains of Bacillus thuringiensis. We show that this assay is useful to detect β-exotoxin in B. thuringiensis with high reliability, helping to discriminate strains that could not be used as bioinsecticides because of their putative risk to humans. Data show that qualitative bioassay with nematodes is a potential alternative to fly larvae bioassays, and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…These The cry1B gene was detected only in strain 237, which also synthesizes β-exotoxin. This association between cry1B subfamily genes and β-exotoxin production has already been reported by Farkaš et al (1977) and Sánchez-Soto et al (2015). Espinasse, Gohar, Chaufaux, et al (2002) and Espinasse, Gohar, Lereclus, and Sanchis (2002) suggested that cry1B and β-exotoxin genetic determinants are located on the same plasmid in some Bt strains, highlighting the production of β-exotoxin, which is linked to the presence of cryogenic plasmids that preferentially harbour the crystalline cry1B protein gene.…”
Section: Discussionsupporting
confidence: 73%
“…These The cry1B gene was detected only in strain 237, which also synthesizes β-exotoxin. This association between cry1B subfamily genes and β-exotoxin production has already been reported by Farkaš et al (1977) and Sánchez-Soto et al (2015). Espinasse, Gohar, Chaufaux, et al (2002) and Espinasse, Gohar, Lereclus, and Sanchis (2002) suggested that cry1B and β-exotoxin genetic determinants are located on the same plasmid in some Bt strains, highlighting the production of β-exotoxin, which is linked to the presence of cryogenic plasmids that preferentially harbour the crystalline cry1B protein gene.…”
Section: Discussionsupporting
confidence: 73%